The moderating effect of peer attachment on hedonistic behavior among Malaysian undergraduate students - Hamzah, Siti Raba'ah; Krauss, Steven Eric; Suandi, Turiman; Hamzah, Azimi; Tamam, Ezhar (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
This article discusses the influence of peer attachment - comprised of communication, trust and alienation - on the relationship between religiosity and religious worldview, and hedonistic behavior among Malaysian undergraduate students. Using Bronfenbrenner’s theory of human ecology and Armsden and Greenberg’s attachment model as a backdrop, this study examines the direct and indirect influence of religiosity and religious worldview on the development of hedonistic behavior as moderated by peer attachment. Drawing on a quantitative survey of 394 Malaysian university students (M age = 21.0, SD = .40), structural equation modeling and path analysis revealed that peer attachment moderated the relationship between religiosity and religious worldview, and hedonistic behavior. The results further showed the unique moderating effect of communication, trust and alienation within peer attachment. Implications from the findings are also discussed.